Komparasi Keterampilan Kolaborasi Siswa Kelas X MAN 2 Kota Padang dengan Menggunakan Model Pembelajaran STAD dan Jigsaw - Wirahmawati, Apriani; Desnita, Desnita; Asrizal, Asrizal; Mufit, Fatni (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2024)
This research is experimental research which aims to see whether there are differences in students' collaboration skills taught using the STAD and Jigsaw learning models. The type of research used in this study was quasi-experimental and non-equivalent control group research design. The population in this study were students of class X MAN 2 Padang City. This research instrument is a collaboration skills assessment sheet. While the data analysis technique used is descriptive analysis technique, normality test, homogeneity test, and hypothesis testing with a significance value of 0.05. According to the results of research data analysis it is known that the average value of collaboration skills in the STAD class is 81.69 higher than that in the Jigsaw class 78.97. Meanwhile, based on the results of testing the hypothesis obtained tcount = 3.487 and ttable = 1.994. In this study tcount is greater than ttable (3.487 > 1.994). Based on this, therefore H1 is accepted and H0 is rejected, which means that there are differences in the improvement of students' collaboration skills taught by the STAD and Jigsaw learning models.